Ocular Phenotyping of Knockout Mice Identifies Genes Associated With Late Adult Retinal Phenotypes - Hang, Abraham; Shao, Andy; Shea, Michael; Roux, Michel J; Imai-Leonard, Denise M; Adams, David J; Amano, Takanori; Amarie, Oana V; Berberovic, Zorana; Bour, Raphaël; Bower, Lynette; Leonard, Brian C; et al. (Investigative ophthalmology & visual science, 2025)
PURPOSE: Analyze phenotypic data from knockout mice with late-adult retinal pathologic phenotypes to identify genes associated with development of adult-onset retinal diseases. METHODS: The International Mouse Phenotyping Consortium (IMPC) database was queried for genes associated with abnormal retinal phenotypes in the late-adult knockout mouse pipeline (49-80 weeks postnatal age). We identified human orthologs and performed protein-protein analysis and biological pathways analysis with known inherited retinal disease (IRD) and age-related macular degeneration (AMD) genes using Search Tool for the Retrieval of Interacting Genes/Proteins (STRING), PLatform for Analysis of single cell Eye in a Disk (PLAE), Protein Analysis Through Evolutionary Relationships (PANTHER), and Kyoto Encyclopedia of Genes and Genomes (KEGG). RESULTS: Screening of 587 late-adult mouse genes yielded 12 with abnormal retinal phenotypes, which corresponded to 20 human orthologs. Three of the 12 mouse genes and two of the 20 human orthologs were previously implicated in retinal pathology or physiology in a literature review. Although all of the genes demonstrated retinal pathology when deleted from the mouse genome, most do not have established roles in human retinal disease. Furthermore, human protein-protein analysis and biological pathway analysis yielded only a few relationships between the candidate gene list and that of known IRD and AMD genes, suggesting they may represent novel retinal functions. CONCLUSIONS: We identified 12 mouse genes with significant late-adult abnormal retinal pathology, eight of which have not been previously implicated in either mouse or human retinal physiology or pathology. These serve as novel retinal disease gene candidates for late-onset retinal disease.
Keywords: retina; Mice; myši knockoutované; Retina; makulární degenerace; Animals; Phenotype; myši; Humans; Macular Degeneration; lidé; Mice, Knockout; Disease Models, Animal; zvířata; fenotyp; oční proteiny; Eye Proteins; modely nemocí na zvířatech